2011
DOI: 10.3945/ajcn.110.002659
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postfortification intake of folate and risk of colorectal cancer in a large prospective cohort study in the United States

Abstract: Background: A higher folate intake is associated with a decreased colorectal cancer risk in observational studies, but recent evidence suggests that excessive folate supplementation may increase colorectal cancer risk in some individuals. Therefore, mandatory folic acid fortification of grain products in the United States may have unintended negative consequences. Objective: We examined the association between folate intake and colorectal cancer risk, including 8.5 y of postfortification follow-up. Design: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 59 publications
5
66
0
1
Order By: Relevance
“…These concerns include increased tumor growth (Cole et al, 2007;Mason et al, 2007;Lawrance et al, 2009), although this has been refuted by other investigations (Gibson et al, 2011;Stevens et al, 2011) and perturbations in immune function (Troen et al, 2006;Halsted, 2008). There is also evidence that high maternal folate concentrations can be associated with greater adiposity and higher insulin resistance in the offspring, which could increase the risk for type 2 diabetes (Yajnik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These concerns include increased tumor growth (Cole et al, 2007;Mason et al, 2007;Lawrance et al, 2009), although this has been refuted by other investigations (Gibson et al, 2011;Stevens et al, 2011) and perturbations in immune function (Troen et al, 2006;Halsted, 2008). There is also evidence that high maternal folate concentrations can be associated with greater adiposity and higher insulin resistance in the offspring, which could increase the risk for type 2 diabetes (Yajnik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that there were between four and six additional cases of CRC per 100 000 of the population post-folic-acid fortification and suggested that the increase could result from an acceleration of progression of adenoma to carcinoma. A more recent prospective cohort study provides some reassurance that the level of folic acid fortification in the US is not detrimental (26) . The authors considered the relative risk of CRC pre-and post-the introduction of folate fortification and found similar inverse associations between the total folate intake and CRC risk both before and after the introduction of mandatory folic acid fortification.…”
Section: Colorectal Cancer and Its Molecular Classificationmentioning
confidence: 99%
“…Large trials of FA supplementation with doses up to 10 times higher than the average intake confirms that such a policy is safe [18,56,67,68]. Reports on increased colon cancer risk that appeared in 1996 almost simultaneously with the approval of food fortification by the FDA [69] were not confirmed later [70] or even by controlled trials using FA supplementation [68,[71][72][73]. Considering results from controlled trials and data from countries applying fortification programs since 1998, there is no evidence that cancer risk can be attributed to or altered by (i.e., increased or decreased) low or moderate intake of FA.…”
Section: Folate Aging and Populationattributable Risk Of Diseasesmentioning
confidence: 96%